PENGARUH BAGI HASIL DAN LOKASI TERHADAP KEPUTUSAN MENABUNG ANGGOTA BMT-UGT SIDOGIRI CAPEM PESANGGARAN KABUPATEN BANGYUWANGI - Hasan, Abil; Sujoko, Edy (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
The purpose of this study is to find out whether the revenue sharing (X1) and location (X2) influence the decision to save members (Y) BMT-UGT Sidogiri Capem Pesanggaran Banyuwangi Regency. This type of research is quantitative with the hypothesis testing research approach, this approach is divided into 3 namely new hypothesis testing research, replication research, replication extension research. In this study using replication research techniques because it examines the hypotheses that have been developed by other researchers and re-tests in different areas or situations. Data analysis using the multiple regression formula manually and also SPSS assistance. The results of the study are the results (X1) and location (X2) significant and positive effect on the decision to save members (Y) BMT-UGT Sidogiri Capanggaran Pesanggaran Banyuwangi Regency.